2021
DOI: 10.1158/1078-0432.ccr-20-4119
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Histopathology Informatics Pipeline for Classification and Prediction of Clinical Outcomes in Subtypes of Renal Cell Carcinoma

Abstract: Purpose: Histopathology evaluation is the gold standard for diagnosing clear cell (ccRCC), papillary, and chromophobe renal cell carcinoma (RCC). However, interrater variability has been reported, and the whole-slide histopathology images likely contain underutilized biological signals predictive of genomic profiles. Experimental Design: To address this knowledge gap, we obtained whole-slide histopathology images and demograp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…According to the experimental process’s cell flow morphology and quantitative phase characteristics, the accuracy can reach 92.56%. Marostica et al (2021) suggested using a deep convolutional neural network for the detection and diagnosis of renal cancer. This method linked the quantitative pathological model with the patient’s genome map and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the experimental process’s cell flow morphology and quantitative phase characteristics, the accuracy can reach 92.56%. Marostica et al (2021) suggested using a deep convolutional neural network for the detection and diagnosis of renal cancer. This method linked the quantitative pathological model with the patient’s genome map and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the less optimal performance of image classifiers for genomic features such as PAM50 status or TP53 mutation status emphasizes that the accuracy of such models is highly dependent on the strength of the morphological signals relative to a particular goal. It is impossible for a model based on optical microscopic images to directly observe an indel or frameshift mutation in a particular gene, but it is possible to observe morphological impacts resulting from or related to a given mutation 11 , 27 . Hence, these models are more likely to find utility in translational systems where the ultimate goal is improving patient diagnosis, prognosis, and treatment stratification, exemplified in this case, by TP53 mutation status, as assessed by an image model, and representing a proxy for the mutation and its causes and consequences, rather than the mutation alone.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, survival analysis has been approached with a classification task by predicting several periods of survival time divided by specific time points 20 . These classifiers, however, cannot model the risk values with certain survival times and lack independent follow-up cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al developed a strategy for integrating histology image and genomic features to predict the outcomes of ccRCC patients from TCGA 19 . Marostica et al diagnosed RCC histological subtypes and predicted stage I ccRCC patients' survival outcomes 20 .…”
Section: Introductionmentioning
confidence: 99%